CLINICAL AND IMMUNOLOGICAL FEATURES OF ALLERGIC DISEASES IN ADOLESCENCE AND YOUTH - Shukurov Botir Bakhodirovich (Journals Park Publishing, 2024)
This article highlights current issues in the study of clinical and anamnestic features of the course of allergic diseases in adolescence and young adulthood.
Keywords: allergic diseases, anamnesis, children, adolescents, immunological characteristics.